Impairment of Wnt11 function leads to kidney tubular abnormalities and secondary glomerular cystogenesis. Issue 1 (December 2016) - Nagy, Irina; Xu, Qi; Naillat, Florence; Ali, Nsrein; Miinalainen, Ilkka; Samoylenko, Anatoly; Vainio, Seppo
Abstract Background Wnt11 is a member of the Wnt family of secreted signals controlling the early steps in ureteric bud (UB) branching. Due to the reported lethality ofWnt11 knockout embryosin utero, its role in later mammalian kidney organogenesis remains open. The presence of Wnt11 in the emerging tubular system suggests that it may have certain roles later in the development of the epithelial ductal system. Results TheWnt11 knockout allele was backcrossed with theC57Bl6 strain for several generations to address possible differences in penetrance of the kidney phenotypes. Strikingly, around one third of the null mice with this inbred background survived to the postnatal stages. Many of them also reached adulthood, but urine and plasma analyses pointed out to compromised kidney function. Consistent with these data the tubules of theC57Bl6 Wnt11 −/− mice appeared to be enlarged, and the optical projection tomography indicated changes in tubular convolution. Moreover, theC57Bl6 Wnt11 −/− mice developed secondary glomerular cysts not observed in the controls. The failure ofWnt11 signaling reduced the expression of several genes implicated in kidney development, such asWnt9b, Six2, Foxd1 andHox10 . AlsoDvl2, an important PCP pathway component, was downregulated by more than 90 % due toWnt11 deficiency in both the E16.5 and NB kidneys. Since all these genes take part in the control of UB, nephron and stromal progenitor cell differentiation, their disrupted expression may contribute to the observed anomalies in the kidney tubular system caused byWnt11 deficiency. Conclusions The Wnt11 signal has roles at the later stages of kidney development, namely in coordinating the development of the tubular system. TheC57Bl6 Wnt11 −/− mouse generated here provides a model for studying the mechanisms behind tubular anomalies and glomerular cyst formation.